The Effect of Selfies on Cosmetic Surgery - Alkarzae, Mohammed; Aldosari, Badi; Alalula, Lama; Almuhaya, Reham; Alawadh, Ibrahim (ENT Updates, 2020)
Objective: Objectives: The present study aimed to evaluate how selfies (self-photographs) are related to cosmetic surgery. Methods: This is a prospective, observational study performed using a self-administered survey. An online questionnaire was distributed through social media to a random sample of 653 individuals from Saudi Arabia aged 18 to 65 years (mean 29.4±10.9 years). 25.1% of respondents were male (164 men), 74.9% were female (489 women). Results: The majority of respondents were satisfied by their appearance in the selfie. 5.8% of respondents stated they had had a cosmetic procedure as a result of self-photography. The procedures involved were: lip fillers, botox, rhinoplasty, cheek fillers, chin implant, scar revision and face-lift. A further 37.8% of respondents expressed a wish to undergo a cosmetic procedure (rhinoplasty, lip fillers, chin implant, scar revision, cheek fillers, botox or facelift) due to selfies. 134 respondents expressed dissatisfaction with their appearance in selfies, 47 of whom (35.1%) expressed an interest in a cosmetic procedure. 46% of those who believed selfies reveal their deformities also wished to have a corrective procedure. Concerning their preferred type of procedure, women chose rhinoplasty, lip fillers, cheek fillers, anti-aging botox, face-lifts and chin implants more often than men. Conclusion: Improvements to body-image through cosmetic surgery outcomes should improve body image and thereby promote self-esteem and socialization. The selfie may underlie the increase in demand for cosmetic procedures and the number of such procedures subsequently undertaken.